Isolation and Characterization of a Novel Thermophilic, Freshwater Methanogen - Harris, Jane E. (1984)
A novel thermophilic, coccoid methanogen isolated from nonthermal freshwater sediments is described. Hydrogen plus carbon dioxide and formate were substrates for methanogenesis, and methane production was stimulated by yeast extract, Casamino Acids, and tryptose. Growth also occurred autotrophically. Elevated levels of sodium chloride were not required for maximum growth and were inhibitory above 2%. The minimum doubling time occurred at 57°C, and the upper and lower limits for methane production were 62 and 26°C, respectively. The optimum pH for growth was between 7.0 and 7.5. Inhibitory antibiotics included metronidazole, anisomycin, chloramphenicol, and lasalocid. Colonies were circular, dark yellow, shiny, and convex with entire edges. Cells were 1 to 2.5 μm in diameter, nonmotile, occurring singly or in pairs, and fimbriated. Cells were lysed by pronase or trypsin digestion, glass-distilled water, and 1% sodium dodecyl sulfate. Electron micrographs of thin sections showed a monolayered cell wall ca. 20 nm thick. The DNA base ratio was 49.2 mol% guanine plus cytosine. The whole cell protein pattern differed from that of other named coccoid methanogens.